Surgical Outcomes After Limb-Sparing Resection and Reconstruction for Pelvic Sarcoma: A Systematic Review. Issue 4 (April 2018) - Wilson, Robert J.; Freeman, Thomas H.; Halpern, Jennifer L.; Schwartz, Herbert S.; Holt, Ginger E.
Abstract : Background: Limb-sparing resection and reconstruction for pelvic sarcomas in multiple small studies have been fraught with complications, reoperations, and impaired patient function. However, the non-oncologic complication and reoperation rates and functional outcomes for patients have never been rigorously compiled, to our knowledge. A systematic review was undertaken to more accurately determine the non-oncologic complication and reoperation rates and functional outcomes for patients after pelvic sarcoma resection and reconstruction. Methods: The review was performed in accordance with PRISMA (Preferred Reporting Items for Systematic Reviews and Meta-Analyses) guidelines. PubMed and Cochrane database searches of English-only studies using the terms "pelvis AND sarcoma" and "pelvis AND sarcoma AND surgery" were performed. Study inclusion criteria were ≥10 patients enrolled, at least 12 months of follow-up, utilization of comparable functional outcome measure(s), and the majority of the resections treating primary bone sarcoma. Results: In this study, 2, 350 studies were reviewed, of which 22 Level-IV studies with a total of 801 patients met inclusion criteria. Reconstructive techniques varied widely and included allografts, allograft-prosthesis composites, saddle prostheses, custom endoprostheses, and irradiated autografts. Pooled means showed a mean 5-year patient survival of 55%. The mean non-oncologic complication rate was 49%. The mean non-oncologic reoperation rate was 37%. The mean Musculoskeletal Tumor Society score was 65%. Conclusions: The non-oncologic complication and reoperation rates for pelvic reconstructions are remarkably high and 5-year survival is poor. Functional outcomes are acceptable but may not be better than a resection of the same Enneking and Dunham type without reconstruction. Consideration should be given to forgoing pelvic reconstruction, especially in patients with poor overall prognosis. Further studies comparing non-oncologic complication rates, reoperation rates, and functional outcomes in patients with equivalent resections treated with or without reconstruction are needed to further elucidate the utility of pelvic reconstruction. Level of Evidence: TherapeuticLevel IV . See Instructions for Authors for a complete description of levels of evidence.